Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

solve the inequality 2(4x-3)>-3(3)+5x

Sagot :

Answer:

[tex]x > -1\\[/tex]

Step by step explanation:

[tex]~~~~~2(4x-3) > -3(3)+5x\\\\\implies 8x-6 > -9+5x\\\\\implies 8x > -9+6+5x\\\\\implies 8x > -3+5x\\\\\implies 8x -5x > -3\\\\\implies 3x > -3\\\\\implies x > -\dfrac 33\\\\\implies x > -1[/tex]